Pengembangan Paket Wisata Usia Dini pada Unkhair’s Tour and Travel - Halida Nuria Marus; dewi Apriani Aco (TEKSTUAL, 2021)
Unkhair Tour and Travel as one of the tour agents engaged in tourism and education at university in North Maluku.  Unkhair Tour and Travel has offered several local tour packages. Tour packages offered to prospective tourists from both students and local communities in Ternate City. From 2018 to 2019, the age category of tourists who are interested in it is the average age of teenagers to adults. It is a challenge for Unkhair Tour and Travel to introduce tourism education for early childhood. This research is Development of Early Age Tourism Packages by Unkhair Tour Travel. The problem in this research is how the development of early childhood tour packages by Unkhair Unkhair Tour and Travel. This research has a general objective, namely how to develop early age tour packages by Unkhair Unkhair Tour and Travel. This research used are marketing theory and using qualitative method. The result of this research is the development of components of tour packages including campus bus transportation, suitable food and drinks for children, decorations for early childhood, tourist objects (historical tours and educational tours), and entertainment. Namely games to get rid of children's boredom during tour trips and guides that come from a student of the Khairun University Travel and Tourism Business Study Program. Development of early childhood travel packages through brochure marketing and social media. Social media which is a means of marketing is the Facebook application through the Unkhair tourism account and WhatsApp through the Unkhair Tour and Travel group.Keywords : development , early age, and  tourism packages.